A necessária formação emancipatória nos cursos de Direito e as habilidades para a prática profissional jurídica: uma análise da avaliação proposta no Exame da OAB - Priscila Frances Uedlih Rios (2019)
The present work investigate the big aspects of education in Law courses, such as legal training, curriculum structure and higher education assessments to ratify (or not) the hypothesis that university expertise based on the accumulation of knowledge become insufficient to the social complexities and transformations promoted by information and communication technologies (ICT), so that legal education is also covered by the crisis of university science. In this scenario is essential to promote emancipatory and humanistic legal training, based on develop in the students skills for professional practice based on critical reflection and autonomy of thought. The student should have an active role in the learning process, in contrast to the spectator figure who has assumed along the course, willing to deal with changes faster and deeper. Considering the reforms that took place in the higher education evaluation system of the last decade, and the constant didactic-pedagogical reflections on legal education and its adequacy to a consistent professional formation, the analysis on the large-scale evaluations or standardized examinations became relevant, which look for obtain indices of performance on the quality of higher and legal education. The evaluations have a fundamental role in guiding decision-making in the context of policies aimed at education, so that not only the ENADE was described in this paper, since it is the official evaluation of the country, but also the OAB source of highly relevant evaluative data for educational reforms and institutional changes often promoted in response to the Exame's own expectations. We have carefully analyzed 80 (eighty) questions from the first stage of the OAB evaluation related to the XXVI Exam of OAB to confirm that students are still required to have memorized knowledge about articles of law and legal norms, which do little to map the development of skills for professional practice in a critical and autonomous way. It is believed that the theoretical contribution is also part of the student's learning, but should be verified in a more complex and transdisciplinary way than currently occurs.